Characteristics of a School-Based Program to Promote Physical Activity in Adolescents and Interventional FrameWork: a Qualitative Study - Mahdi Sepidarkish; Saharnaz Nedjat; Leila Haghjou; Leila Mounesan; Fatemeh Shokri; Amir Almasi-Hashiani; Reza Majdzadeh (Iranian Association of Health Education and Health Promotion, 2017)
Background and Objective: Lack of exercise is inconsistent with healthy lifestyle. In recent years, it has increased in different age groups, particularly in children and adolescents. To implement any health program, we should have a deep understanding of the health program. This study aimed to recognize characteristics of a school-based program for promoting physical activity in adolescents from the perspective of experts and health authorities, as well as student and parent's overviews. Also, implementation and integration of this program was investigated by faculty members and connoisseurs' perspectives Methods: The qualitative study was performed through in-depth interviews and Focus group discussion (FGD) on faculty members, experts of different ministries and students and parents. Overall, 24 experts, and 6 faculty members and connoisseurs participated in the study. Also, four FGD were held with students and parents. The findings were examined using content analysis Results: The results were divided in two parts: A) Existing problems and characteristics of a school-based intervention program for promoting physical activity from the perspective of students, parents and experts of different ministry B) implementation and integration of the program by faculty members and connoisseurs' perspectives. Totally, we identified 3 categories and 28 themes for the section A, and 2 categories and 22 themes for the section B. The following three domains were extracted for the section A including management problems, shortage of resources, and approaches of increasing physical activity. Two domains for the section B were barriers to intersectorial coordination and characteristics of a school-based program. The results of the interviews with faculty members and health authorities led to identify a twentieth-stage framework for implementing the program. Conclusion: The results indicated a severe lack of human and financial resources, and a coherent and systematic program to promote physical activity in schools. The identified framework can be used for implementing other health interventions.